Information culture and media literacy in the structure of the library cultural and educational activities - T. B. Kavalerchik (Bibliosphere, 2020)
Due to the active expansion of the media environment, convergent processes occurring in the modern socio-cultural space, there is a need to create information and educational platforms on forming information culture of population and, in particular, school-age children. The article describes the results of a study on creating favorable cultural and educational conditions for organizing systematic work on information culture and media literacy formation for children of middle and high school age in a library. The goal of the study is to build a universal model of the educational program with its subsequent implementation in the library environment. Its tasks were: 1) to make experiments on testing interactive lessons on the course «Information Culture in the Study of the Native Land Literature», developed according to the proposed universal model; 2) to analyze the results of experimental work; 3) to design the development program for the Information and Digital Culture Center of the Sakhalin Regional Universal Scientific Library for it to form information culture and media literacy for various population groups, in particular, the young generation. The article assesses the significance of the problem, describes the research parameters, and presents the results of testing the course "Information culture in the study of literature of the native land». The development program of the center for information and digital culture of the Sakhalin Regional Universal Scientific Library was made, designed to solve the problem of forming the information culture of the younger generation.